Efficacy of Lignocaine in Three Different Routes In Attenuation of Haemodynamic Response Associated With Endotracheal Intubation : A Comparative Study (Journal of Chittagong Medical College Teachers' Association, 2020)
Background: Transient haemodynamic instability i.e tachycardia and hypertension is an inevitable outcome of laryngoscopy and endotracheal intubation which can have serious effects in patients with COPD, IHD or hypertension that can lead to ischaemia, infarction, arrhythmia or cardiac arrest in vulnerable patients. Administration of lignocaine is one of the techniques used to attenuate haemodynamic response associated with endotracheal intubation. The present study was designed to compare the changes in blood pressure and heart rate that occur before and after the endotracheal intubation in three different routes intravenous( i.v.) local spray over laryngeal inlet or nebulization.Materials and methods : It was a randomized double blind clinical trial. It was conducted at the Department of Anaesthesiology, Chittagong Medical College Hospital, Chattogram from July 2005 to June 2007. A total of one hundred and fifty adult patients (ASA I, Mallampati grade 1 & 2) scheduled for elective surgery under general anaesthesia wereselected. Patients were randomly allocated in three groups A,B and C, by lottery .Group A received 2% lignocaine i.v., Group B received 10% lignocaine spray over the laryngeal inlet and vocal cords and group C patients were nebulized with 2% lignocaine solution.Results: The rise in Systolic, Diastolic and mean arterial pressure with local spray was significantly lower than with intravenous and nebulized group and the rise in heart rate was significantly lower with local spray group than with nebulization group and intravenous group. Data were processed using software SPSS version 11.5. The test statistics used to analyse the data were Chi-squire(c2) test and Anova.Conclusion: The findings of this study reflects the local spray of 10% lignocaine over laryngeal inlet prior to intubations attenuates the rise in blood pressure and heart rate more than intravenous administration of lignocaine or nebulization of lignocaine.JCMCTA 2019 ; 30 (2) : 86-91